Pengembangan Flipbook Digital "FIKIR" tentang Keteladanan Rasulullah SAW pada Pembelajaran PAI Kelas 3 SD - Zuniar, Meutia; Rahmadani, Mabda; Hapsyari, Stefi Sri; Aeni, Ani Nur (YASIN, 2025)
The widespread use of advanced technology over time has driven significant changes in teaching strategies, prompting education to adapt through the implementation of technology based learning media. Islamic Religious Education (PAI) plays an important role in aligning students’ competency development with their characteristics by utilizing technology as an innovative learning medium that does not detach students from the digital world. This study aims to analyze the development of the digital flipbook “FIKIR” as an innovative learning medium to enhance students’ knowledge through an engaging approach. The method used is Design and Development research with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation results from subject matter and media experts show that the digital flipbook “FIKIR” falls into the category of highly suitable for use. Field trials indicate that most students reported the medium as helpful in supporting their learning process effectively. The conclusion of this study is that the development of the digital flipbook “FIKIR” has a positive impact on PAI learning, particularly for third grade students at SD Hegarmanah, and has the potential to become an adaptive and applicable technology based learning medium in primary education.